THE APPLICATION OF ISLAMIC LAW AT THE COLONIAL AGE AND IT'S IMPLICATION FOR THE INDONESIAN RELIGIOUS JUSTICE SYSTEM - Mas’ud, Muhamad (Journal of Islamicate Studies, 2019)
The enactment of Islamic law during colonialism was marked by the thought of Sayyid Usman, a historical figure who had a great interest in the study of Islamic law in Indonesia during the Dutch East Indies colonization. As a scholar, he has special attention to the continuity of Islamic law in Indonesia, especially regarding Islamic family law, which at that time had been widely practiced by people to replace customary law. In addition, he also contributed a lot of thoughts in the context of enforcing Islamic law by organizing religious justice institutions and compiling Islamic family law. Formally the institutions of religious justice, especially in Java and Madura, were only formed by the Dutch East Indies government in 1882, through the Staatsblad 1882 No. 152. This formation is at once a measure of the reorganization of religious justice institutions, namely by establishing new religious courts in addition to each landraad (the same court) with the same legal area, on average as large as the district. It's just that if before the religious court was independent, then with this reorganization the power to carry out the verdict was handed over to landraad. K.F. Holle, L.W.C. Van den Berg, and Snouck Hurgronje, these three Dutch people were very influential in the birth of the theory of the enactment of Islamic law in Indonesia, L.W.C. Van den Berg is one of the initiators of the theory of receptio in complexu, which states that "for Muslims full Islamic law applies because he has embraced Islam even though there are still deviations in its implementation. Next to L.W.C. Van den Berg carries the theory of receptio in complexu, and Snouck Hurgronje as the originator of receptie theory, which states that for indigenous people basically customary law applies, and Islamic law applies to indigenous people if Islamic legal norms have been accepted by society as customary law.